Global Citizenship Education in Social Studies: Experiences of Turkish Teachers and Students in International Conflict and War - Arife Figen Aksoy (Anı Publishing, 2013)
With the impact of the media, international conflicts are increasingly becoming a part of both everyday life and global citizenship education. The purpose of this research was to understand the perceptions of students and teachers about the incidents of international conflict and war, how teachers present these issues in social studies course, and the problems teachers encounter in this process. This study was carried out as a qualitative case study research. The data were collected by participant observations carried out in Social Studies lessons and by semi-structured interviews with the participating teachers and students. The data were analyzed using interpretive thematic analysis. The findings from this study revealed that the teachers in this study acted in protective, emotional, rational and tentative modes while teaching the issues of international conflict and war. The study also found that the teachers' behaviors while teaching controversial issues had an influence on the students' knowledge, skills and attitudes on the subject. In addition, the students' age and maturity level, gender, socio-economic and cultural level had an influence on learning about these issues. Finally, the findings indicated that the teachers who participated in this study did not have sufficient knowledge and experience in teaching controversial issues and international conflict and war.